Are on-time performance statistics worthless? An empirical study of the flight scheduling strategies of Brazilian airlines. (January 2021) - Eufrásio, Ana Beatriz R.; Eller, Rogéria A.G.; Oliveira, Alessandro V.M.
Highlights: We develop a method to decompose the extra schedule block times into operational and strategic factors. We estimate the impact of extra times on flight delays, allowing for the moderation effects. We test the hypothesis of the existence and effectiveness of schedule padding. Abstract: Airlines may manage their on-time performance by lengthening schedules with engineered increases in planned flight times. We develop an econometric model of high dimensional sparse (HDS) regression to decompose the extra schedule block times into operational and strategic factors. We estimate the impact of extra times on flight delays, allowing for the moderation effects of runway congestion, slots, and propagated delay. We test the hypothesis of the existence and effectiveness of schedule padding practices. We find that a 2012 on-time disclosure rule may have induced carriers' padding behavior. In contrast, slot regulation may prevent the formation of extra block times.